Major Research Issues in Religious Tourism - Jackowski, Antoni; Sołjan, Izabela (Turyzm/Tourism, 2008)
The article deals with terminology issues in religious tourism. The importance of pilgrimage in the contemporary world is highlighted, as well as those elements which determine the phenomenon. Research concepts in religious tourism are analysed theoretically and relations between religious tourism and pilgrimage are presented. The need to draw a precise definition of religious tourism and to determine its research area is also stressed.